Comparison of G protein sequences of South African street rabies viruses showing distinct progression of the disease in a mouse model of experimental rabies - (:unkn) unknown (My University, 2017)
Rabies is a fatal zoonotic disease and infections generally lead to a fatal encephalomyelitis in both humans and animals. In South Africa, domestic (dogs) and the wildlife (yellow mongoose) host species maintain the canid and mongoose rabies variants respectively. In this study, pathogenicity differences of South African canid and mongoose rabies viruses were investigated in a murine model, by assessing the progression of clinical signs and survivorship. Comparison of glycoprotein gene sequences revealed amino acid differences that may underpin the observed pathogenicity differences. Cumulatively, our results suggest that the canid rabies virus may be more neurovirulent in mice than the mongoose rabies variant.
Keywords: African Research